1980
DOI: 10.1093/ajcn/33.12.2686
|View full text |Cite
|
Sign up to set email alerts
|

Total body water measurement in humans with 18O and 2H labeled water

Abstract: Deuterium or tritium labeled water traditionally has been used for the measurement of total body water by application of the dilution principle. However, these methods have not enjoyed wide clinical use. The use of deuterium is hampered by the tedious and time consuming nature of the analysis while the use of tritium involves a radiation hazard. In addition, exchange of the label with nonaqueous hydrogen in the body raises questions about the accuracy of total body water values. To determine if water labeled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
382
2
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(397 citation statements)
references
References 23 publications
7
382
2
6
Order By: Relevance
“…This study therefore compared TBW predicted by foot-to-foot BIA with those measured using a deuterium oxide dilution technique. Deuterium oxide dilution is accepted as one of the 'gold standard' techniques for measuring TBW (Sheng & Huggins, 1979), although the measured dilution space needs to be corrected for overestimation of TBW because of the exchange of isotope with nonaqueous hydrogen (Schoeller et al, 1980). In our laboratory, in vitro tests have shown that the accuracy of deuterium dilution for measuring a water volume is approximately 1%.…”
Section: Discussionmentioning
confidence: 99%
“…This study therefore compared TBW predicted by foot-to-foot BIA with those measured using a deuterium oxide dilution technique. Deuterium oxide dilution is accepted as one of the 'gold standard' techniques for measuring TBW (Sheng & Huggins, 1979), although the measured dilution space needs to be corrected for overestimation of TBW because of the exchange of isotope with nonaqueous hydrogen (Schoeller et al, 1980). In our laboratory, in vitro tests have shown that the accuracy of deuterium dilution for measuring a water volume is approximately 1%.…”
Section: Discussionmentioning
confidence: 99%
“…We have compared the predicted total body water from a new foot-to-foot impedance machine to that measured via a deuterium oxide dilution technique. The latter technique is accepted as one of thè gold standard' methods for measuring total body water (Sheng & Huggins, 1979), although it is important to correct the measured dilution space for the overestimation of total body water due to exchange of isotope with nonaqueous hydrogen (Schoeller et al, 1980). In our laboratory, in vitro tests have shown that the accuracy of deuterium dilution for measuring a water volume is approximately 1%.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for measuring body composition in a two-compartment model has been underwater weighing (UWW), which measures body density from which fat and lean mass content are estimated by assuming standard ®gures for density of these components (Siri, 1961). Other robust methods include the total-body potassium method, measuring intracellular¯uid by detecting the natural radioactive 40 K isotope (Boddy et al, 1972), and measurement of total body water by dilution of a deuterium-labeled water dose (Schoeller et al, 1980). More complicated multicompartment models of body composition that include bone mass are under development (Harsha & Bray, 1996).…”
Section: Introductionmentioning
confidence: 99%